Pancatransformasional Leadership in Madrasahs: Integrating Religious Values for Sustainable Environmental Education through Adiwiyata Programs - Yaqin, Firdaus Ainul; Mulyadi, Mulyadi; Marno, Marno (JURNAL AL-TANZIM, 2025)
This study aims to analyze the characteristics of the transformational leadership of the madrasah principal in the development of Madrasah Adiwiyata. This study uses a qualitative approach of the case study type through a multi-site approach. Data collection techniques include in-depth interviews, participatory observation, and documentation. Data analysis techniques use an interactive model consisting of four stages: data collection, data presentation, data condensation, and concluding. The study results indicate that The 4 "I's" of Transformational Leadership are refined into Pancatransformational by adding elements of Idealized Religious Influence. Pancatransformational in madrasah leadership includes Religious Influence, Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individualized Consideration with leadership principles based on wasathiyah/moderate religious values that can realize the development of a more holistic Adiwiyata school program. The implications of this study indicate that the concept of Pancatransformational, with elements of Idealized Religious Influence, strengthens the implementation of the Adiwiyata program in madrasahs. Based on wasathiyah/moderate values, this leadership integrates religious values in environmental conservation efforts. It motivates the entire school community to participate actively, creating an inclusive and sustainable school culture.